The Role of DmCatD, a Cathepsin D-Like Peptidase, and Acid Phosphatase in the Process of Follicular Atresia in Dipetalogaster maxima (Hemiptera: Reduviidae), a Vector of Chagas' Disease - Leyria, Jimena (2015)
In this work, we have investigated the involvement of DmCatD, a cathepsin D-like peptidase, and acid phosphatase in the process of follicular atresia of Dipetalogaster maxima, a hematophagous insect vector of Chagas' disease. For the studies, fat bodies, ovaries and hemolymph were sampled from anautogenous females at representative days of the reproductive cycle: pre-vitellogenesis, vitellogenesis as well as early and late atresia. Real time PCR (qPCR) and western blot assays showed that DmCatD was expressed in fat bodies and ovaries at all reproductive stages, being the expression of its active form significantly higher at the atretic stages. In hemolymph samples, only the immunoreactive band compatible with pro-DmCatD was observed by western blot. Acid phosphatase activity in ovarian tissues significantly increased during follicular atresia in comparison to pre-vitellogenesis and vitellogenesis. A further enzyme characterization with inhibitors showed that the high levels of acid phosphatase activity in atretic ovaries corresponded mainly to a tyrosine phosphatase. Immunofluorescence assays demonstrated that DmCatD and tyrosine phosphatase were associated with yolk bodies in vitellogenic follicles, while in atretic stages they displayed a different cellular distribution. DmCatD and tyrosine phosphatase partially co-localized with vitellin. Moreover, their interaction was supported by FRET analysis. In vitro assays using homogenates of atretic ovaries as the enzyme source and enzyme inhibitors demonstrated that DmCatD, together with a tyrosine phosphatase, were necessary to promote the degradation of vitellin. Taken together, the results strongly suggested that both acid hydrolases play a central role in early vitellin proteolysis during the process of follicular atresia.